The genus Astylosternus in the Upper Guinea rainforests, West Africa, with the description of a new species (Amphibia: Anura: Arthroleptidae) - Rödel, Mark-Oliver; Barej, Michael F.; Hillers, Annika; Leaché, Adam D.; Kouamé, N’goran G.; Ofori-Boateng, Caleb; Assemian, N. Emmanuel; Tohé, Blayda; Penner, Johannes; Hirschfeld, Mareike; Doumbia, Joseph; Gonwouo, Legrand Nono; et al. (Zootaxa, 2012)
Astylosternus laticephalus sp. nov. Rödel, Hillers, Leaché, Kouamé, Ofori-Boateng, Diaz & Sandberger is described fromeastern Ivory Coast and western and central Ghana, and compared to Astylosternus occidentalis Parker, 1931 from thewestern part of the Upper Guinea forest zone (western Ivory Coast, Liberia, Guinea and Sierra Leone). Based on a com-prehensive sample, including specimens from the entire range, the latter species is re-described. The new species is char-acterized by a body shape typical for frogs of the genus Astylosternus, but has an exceptionally broad head, i.e. broaderthan in A. occidentalis. The basic dorsal pattern of A. laticephalus sp. nov. consists of a brownish to brownish red colour-ation with distinct red dots (red dots are only rarely present in A. occidentalis). The new species has bicoloured eyes withthe lower part of the iris being grey, the upper third of the iris is orange to red (A. occidentalis always has a uniform greyishiris). Males of the new species lack spines on the throat, belly (always present in A. occidentalis males), and a layer ofblack nuptial skin in the pectoral region (present in male A. occidentalis from western Guinea). Astylosternus laticephalussp. nov. differs from A. occidentalis by a mean pairwise genetic distance of 3.2% in the investigated part of the mitochon-drial 16S rRNA gene. Genetic divergence to the morphologically most similar Central African species, A. diadematus,was 11.9%. We briefly discuss the phylogenetic position of West African Astylosternus, hint on the possibility that thegenus might be paraphyletic and discuss the biogeography of West African Astylosternus, in particular with respect to forest cover fluctuations in the past.